It's a surprising change that I'm doing my homework.Would some math wizard/anyone who passed Grade 9 Mathematics answer me this?
Have I done this question right?
3x - (x + 4) = -x + 83x - 4x = -x + 83x - 4x + x = 8x = 8
[Edited by yosup, 3/11/2009 4:37:07 PM]
Nope. The second step, you multiplied x and 4. You should have added.
Should look like this.
3x - (x + 4) = -x + 8-(x + 4) = -4x + 8-x - 4 = -4x + 8-4 = -3x + 83x = 12
x = 4
Ah, yes.I knew I was missing something.
I don't like the way you did that Thrawn.>_>
I can't help it.
3x - (x + 4) = -x + 83x - x - 4 = -x + 82x - 4 = -x + 83x = 12x = 4
I set mine up this way:
I'm no expert at math, but that looks correct to me.